Rekonstruksi Hukum Perkawinan Lintas Agama: Analisis Tafsir Tematik dan Ushul Fikih - Fakih, Zainun Kamaluddin (Faculty of Ushuluddin UIN Syarif Hidayatullah Jakarta, 2025)
This article re-examines the Islamic prohibition of interfaith marriage through a combined thematic-tafsīr and uṣūl al-fiqh lens. It scrutinises three key Qurʾanic loci: (1) al-Baqarah 2:221, which restricts marriage with pre-Islamic Arab mushrikūn; (2) al-Mumtahanah 60:10, revealed after the 628 CE Ḥudaybiyyah treaty and conditioned by warfare; and (3) al-Māʾidah 5:5, which permits unions with the People of the Book. Philological analysis demonstrates that the term mushrik is not synonymous with Ahl al-Kitāb, so the Qurʾanic ban is context-bound rather than an absolute proscription on all non-Muslims. By critiquing classical ijtihād principles, the study argues that the prevailing proscription on Muslim women marrying non-Muslim men stems from sociopolitical considerations rather than unequivocal textual evidence and is therefore amenable to re-ijtihād in contemporary plural societies. The paper concludes that reconstructing a more inclusive fiqh of interfaith marriage is necessary to safeguard communal welfare and mitigate potential societal discord.